Application of STATCOM-HTS to Improve DFIG Performance and FRT during IGBT Short Circuit - Abdou, A.; Pota, H.; Abu-Siada, Ahmed; Alharbi, Yasser Mohammed R (IEEE, 2014)
A little attention has been paid to the faults within the converter switches of a wind energy conversion system (WECS). Solutions suggested in the literature to improve the performance of a WECS rely on compensating the reactive power at the point of common coupling (PCC) to maintain the PCC voltage within the limits specified by the grid codes. Recently, transmission line operators have expanded WECS codes to include active power support to the grid during fault conditions. Therefore, to maintain the connection of a wind turbine during various disturbance events, it is essential to fulfil grid codes. This paper introduces a new application for a static synchronous compensator (STATCOM) equipped with a high-temperature superconducting coil (HTS) to compensate both active and reactive powers at the PCC during short-circuit events within the insulated-gate bipolar transistor (IGBT) switches of the grid side converter (GSC) of a doubly-fed induction generator (DFIG)-based WECS. Compliance of the voltage profiles of the DFIG with the fault ride-through (FRT) specified in the recent grid codes of the USA, and Spain, with and without the proposed controller, is examined. Simulation results show that the proposed controller can bring the active and reactive power at the PCC to their nominal steady-state levels during studied fault.